(untitled) (Current Horticulture, 2024)
China is a global leader in mushroom production. The mushrooms are grown in China since ancient times. In changing scenario, is cultivation shifted from traditional mushroom towards specialty mushroom during last few decades. More consumption and export demands are responsible for this shift. Nevertheless, Indiais also picking pace in mushroom with lukewarm response. Awareness and other social constraints prevailing in India might be one of the reasons responsible for that. Moreover during last 4 decades, extensive research on mushroom has promoted mushroom in India. With five major and few exotic mushrooms, India slowly is increasing its market share. To be successful in both domestic and export markets, it is essential for Indian growers to produce quality mushrooms and mushroom-fortified value-added products at competitive rates without any agro-chemical residues.